2016
DOI: 10.1371/journal.pone.0165189
|View full text |Cite
|
Sign up to set email alerts
|

Duloxetine Inhibits Microglial P2X4 Receptor Function and Alleviates Neuropathic Pain after Peripheral Nerve Injury

Abstract: P2X4 receptors (P2X4R) are a family of ATP-gated non-selective cation channels. We previously demonstrated that activation of P2X4R in spinal microglia is crucial for neuropathic pain, a highly debilitating chronic pain condition, suggesting that P2X4R is a potential therapeutic target for treating neuropathic pain. Thus, the identification of a compound that has a potent inhibitory effect on P2X4R is an important clinical challenge. In the present study, we screened a chemical library of clinically approved d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 53 publications
2
38
0
Order By: Relevance
“…are among the most commonly prescribed pharmacological treatments for FM, and show moderate effectiveness in reducing some FM symptoms (Welsch et al, 2018). While the primary mechanism of action of SNRIs is to normalize concentrations of endogenous monoamine neurotransmitters, which are thought to be imbalanced in FM (Albrecht et al, 2016; Kosek et al, 2016; Russell et al, 1992; Wood, 2008), one potential additional mechanism may be glial modulation, as both duloxetine (Yamashita et al, 2016) and milnacipran (Shadfar et al, 2018) attenuate microglial activation in animal models. Interestingly, among the regions demonstrating neuroimmune activation in our current study were the PCC/precuneus, a core region of the default mode network, where post-treatment changes in pain related activation were specifically related to the degree of positive clinical response to milnacipran treatment in fibromyalgia patients (Jensen et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…are among the most commonly prescribed pharmacological treatments for FM, and show moderate effectiveness in reducing some FM symptoms (Welsch et al, 2018). While the primary mechanism of action of SNRIs is to normalize concentrations of endogenous monoamine neurotransmitters, which are thought to be imbalanced in FM (Albrecht et al, 2016; Kosek et al, 2016; Russell et al, 1992; Wood, 2008), one potential additional mechanism may be glial modulation, as both duloxetine (Yamashita et al, 2016) and milnacipran (Shadfar et al, 2018) attenuate microglial activation in animal models. Interestingly, among the regions demonstrating neuroimmune activation in our current study were the PCC/precuneus, a core region of the default mode network, where post-treatment changes in pain related activation were specifically related to the degree of positive clinical response to milnacipran treatment in fibromyalgia patients (Jensen et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The current study has shown that three nonselective compounds, duloxetine, paroxetine, and TNP‐ATP, can inhibit canine P2X4 receptors. The selective 5‐HT reuptake inhibitor, paroxetine, and the 5‐HT‐noradrenaline reuptake inhibitor, duloxetine, are reported to non‐selectively inhibit human and rodent P2X4 receptors (Nagata et al, 2009; Yamashita et al, 2016), as well as to alleviate allodynia in models of chronic pain (Iyengar, Webster, Hemrick‐Luecke, Xu, & Simmons, 2004; Zarei, Sabetkasaei, & Moini Zanjani, 2014). Consistent with these previous studies, both compounds demonstrated effective inhibition of canine and human P2X4 receptors in our models, albeit at relatively high concentrations (>100 μM).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, NP-1815-PX had poor penetration to the CNS tissues, but the pharmaceutical company Nippon Chemiphar successfully developed a more potent and specific P2X4R antagonist with CNS-penetrating properties (NC-2600), which are now under clinical trials in Japan. 11) Furthermore, recent studies developed monoclonal antibodies for extracellular head domains of P2X4Rs, [109][110][111] a region that is an important site for modulation of this receptor. 45) Among the developed antibodies, immunoglobulin G (IgG)#191-Bbbt0626 produced dose-dependent and long-lasting analgesia (for at least seven days) in a neuropathic pain model when given subcutaneously.…”
Section: Development Of Microglia-targeting Drugsmentioning
confidence: 99%
“…45) Among the developed antibodies, immunoglobulin G (IgG)#191-Bbbt0626 produced dose-dependent and long-lasting analgesia (for at least seven days) in a neuropathic pain model when given subcutaneously. 111) In addition, a chemical screening of a library identified the antidepressant duloxetine as a clinically approved drug that has an inhibitory effect on rodent and human P2X4R and a reversal effect on the PNI-induced mechanical allodynia. 112) For drugs controlling ATP release, the first-generation bisphosphonate clodronate was identified as a potent and selective allosteric inhibitor for VNUT.…”
Section: Development Of Microglia-targeting Drugsmentioning
confidence: 99%